2016
DOI: 10.1016/j.aquaculture.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress biomarkers reveal stocking density effects in late larval Delta Smelt (Hypomesus transpacificus)

Abstract: Suboptimal fish stocking densities in experimental systems may elicit stress responses that can affect experimental results. Fish species, age and size, water chemistry and flow, and physical characteristics of the experimental system (e.g., tank, cage) are among the parameters to be considered when determining stocking densities. However, systematic studies to define fish densities minimizing stress in experimental systems are rarely performed. This is particularly true when working with species of low aquacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Isoflavones may alter endocrine functions and, as exogenous compounds that could be present in high dose in feed, may induce stress in fish. Cortisol is a biomarker to evaluate the state of stress in fish (Bertotto et al., ; Hasenbein, Fangue, Geist, Komoroske & Connon, ) as well as in other vertebrates. At the end of the trial, plasma, muscle and fin cortisol concentrations were not significantly different in the trouts fed different diets.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavones may alter endocrine functions and, as exogenous compounds that could be present in high dose in feed, may induce stress in fish. Cortisol is a biomarker to evaluate the state of stress in fish (Bertotto et al., ; Hasenbein, Fangue, Geist, Komoroske & Connon, ) as well as in other vertebrates. At the end of the trial, plasma, muscle and fin cortisol concentrations were not significantly different in the trouts fed different diets.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is challenging to unravel the specific cause underlying acclimation time effects, wild fish during development may undergo confinement stress with an increase in the cortisol stress hormone, a well-documented occurrence in teleost fishes (Barton and Iwama, 1991;Bonga, 1997). Furthermore, previous studies have shown that laboratory conditions, such as tank color and densities of fish held together, can affect behavior and physiology (Brown et al, 1992;Pavlidis et al, 2013;Hasenbein et al, 2016). For example, when held in lower densities, Arctic char (Salvalinus alpinus) exhibited altered swimming behavior and more aggressive interactions (Brown et al, 1992).…”
mentioning
confidence: 99%
“…More negative interactions between fish are suggested to increase energetic demands (Brown et al, 1992). Stress markers were also significantly greater in late larval delta smelt (Hypomesus transpacificus) held at lower densities of 7 and 14 individuals compared with higher densities of 28 and 49 (Hasenbein et al, 2016). Here, 39 fish were initially placed in each P CO2 triplicate bucket, after which nine fish were sequentially removed for sampling metrics.…”
mentioning
confidence: 99%
“…We chose this experimental design because delta smelt are schooling, pelagic fish that experience high stress and mortality if cultured, acclimated, or exposed individually or in small groups (Hasenbein et al. ), recognizing the tradeā€off of possible small tank effects in this component of the study. Containers were placed into a water bath to maintain temperature at 15.4Ā°C (Ā±0.42 SD).…”
Section: Methodsmentioning
confidence: 99%